Method for producing oligomeric dextrose and lignin by using corn cob residues

Through the reaction of zinc bromide molten brine hydrate with xylos slag powder, the problem of difficult to efficiently treat xylos slag in the prior art is solved, and a high yield of oligoglucose and lignin production is achieved, with good economic and environmental benefits.

CN120082677APending Publication Date: 2025-06-03QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510236104.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and highly value-added cellulose and lignin in xylose slag, resulting in waste of resources and environmental pollution.

Method used

The zinc bromide molten brine hydrate is used to react with xylose slag powder, and the hydrolysis of cellulose is achieved to generate oligoglucose and lignin by regulating the molar ratio of zinc bromide to water and reaction conditions.

Benefits of technology

The production of oligoglucose and lignin with high yields (up to 61.7 wt% and up to 95.8% lignin yields) has been achieved, which simplifies the separation process and can reuse inorganic salts, which has good economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120082677A_ABST
    Figure CN120082677A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of biomass resource utilization, and particularly relates to a method for producing oligodextrose and lignin by using corn cob residues, which comprises the following steps: (1) drying the corn cob residues, and crushing until the particle size is 0.1-1mm to obtain corn cob residue powder; (2) adding the corn cob residue powder into a zinc bromide molten salt hydrate, reacting at 80-110 DEG C for 20-60 minutes, and after the reaction is completed, filtering and separating to obtain a liquid phase containing glucose and oligomeric glucose and a solid phase rich in lignin; the polymerization degree distribution range of the obtained oligosaccharide is 2-12. The method is short in separation time, simple and easy to implement, inorganic salt can be recycled, high-valued comprehensive utilization of biomass resources is achieved, and good economic and environmental benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomass resource utilization, and particularly relates to a method for producing oligosaccharide glucose and lignin from xylose residues. Background Art

[0002] Xylose residues are the residues after extracting xylose from corncobs, which contain rich components such as cellulose and lignin. If not reasonably utilized, it is easy to cause environmental pollution. At present, the treatment methods for xylose residues are limited, and it is difficult for traditional processes to efficiently and highly value-added convert various components therein.

[0003] Molten salt hydrates are a kind of ionic liquid-like system. Compared with traditional ionic liquids, they have the advantages of low price, simple preparation, no volatility, non-toxicity, and environmental friendliness. In recent years, molten salt hydrate systems have attracted great attention in the field of biomass refining. Molten salt hydrates have good solubility and hydrolysis ability for polysaccharides such as cellulose, and can degrade cellulose into monosaccharides in a homogeneous system. However, sugar molecules have a high solubility in molten salt hydrate systems (MSHs), and the subsequent separation and purification of monosaccharide products from the hydrolysis solution are relatively difficult, which limits the application of molten salt hydrate systems in lignocellulose refining. And oligosaccharide glucose has a relatively larger molecular weight than glucose and is easier to separate from molten salt hydrates. The reaction of using molten salt hydrates to treat cellulose to produce oligosaccharide glucose has relatively strict requirements on conditions such as temperature, pressure, and reaction time. Too high a temperature may lead to an increase in side reactions, such as excessive degradation of cellulose to produce other by-products; too low a temperature will result in a slow reaction rate and a decrease in yield. If the reaction time is too short, the hydrolysis of cellulose is incomplete and the yield of oligosaccharide glucose is low; if the reaction time is too long, the oligosaccharide glucose that has been generated may be further degraded into glucose. At the same time, different molten salt hydrates have different physical and chemical properties, and their solubility and hydrolysis ability for cellulose also vary. Selecting a suitable molten salt hydrate is the key. The main components of xylose residues are complex polysaccharides such as cellulose, and due to their complex composition, it further increases the treatment difficulty of molten salt hydrates.

[0004] As a functional oligosaccharide with various physiological functions, the demand for oligosaccharide glucose is increasing in the fields of food, medicine, etc.; lignin also has broad application prospects in materials, chemical engineering, etc. Therefore, developing an innovative method for simultaneously preparing oligosaccharide glucose and lignin from xylose residues with the help of molten salt hydrates has extremely high economic value and environmental significance. Summary of the Invention

[0005] To overcome the deficiencies of the above-mentioned prior art, the present invention provides a method for producing oligosaccharide glucose and lignin from xylose residues. The method provided by the present invention can realize the production of oligosaccharide glucose and lignin from xylose residues, has a relatively high yield, and can achieve the high-value comprehensive utilization of biomass resources.

[0006] In view of this, the present invention provides a method for producing oligosaccharide glucose and lignin from xylose residue, and the method comprises the following steps:

[0007] (1) After drying, the xylose residue is crushed to a particle size of 0.1-1 mm to obtain xylose residue powder;

[0008] (2) The xylose residue powder is added to zinc bromide molten salt hydrate, and reacted at 80-110 °C for 20-60 minutes. After the reaction is completed, filtration and separation are carried out to obtain a liquid phase containing glucose and oligosaccharide glucose and a solid phase rich in lignin; the oligosaccharide glucose in the liquid phase is precipitated by organic alcohol, and the polymerization degree distribution range of the obtained oligosaccharide glucose is 2-12, and the solid phase is washed and dried to obtain lignin;

[0009] Preferably, the zinc bromide molten salt hydrate is ZnBr 2 ·3-5H 2 O.

[0010] Preferably, the polymerization degree distribution range of the oligosaccharide glucose is 3-8.

[0011] Preferably, the purity of the lignin is greater than 96%, and the yield is greater than 94 wt%.

[0012] Preferably, in the step (2), the mass-volume ratio of the xylose residue powder to the zinc bromide molten salt hydrate is 1:10-30, g / mL, preferably 1:20, g / mL.

[0013] Preferably, in the step (2), the molar ratio of zinc bromide to water in the zinc bromide molten salt hydrate is 1:3-5, preferably 1:4.

[0014] Preferably, in the step (2), the reaction temperature is 80-110 °C, and the reaction time is 20-60 minutes. Further preferably, the reaction temperature is 100 °C, and the reaction time is 40 minutes.

[0015] Preferably, in the step (2), the organic alcohol is one of methanol, ethanol, propanol or butanol.

[0016] Preferably, in the step (2), the organic alcohol is methanol.

[0017] Preferably, in the step (2), the liquid after precipitating the oligosaccharide glucose is treated with a dialysis bag with a molecular weight of 100, the liquid outside the dialysis bag is collected, and the organic alcohol and water therein are removed by rotary evaporation to recover zinc bromide for reuse.

[0018] Preferably, in the step (2), the solid part obtained by filtration is washed with distilled water.

[0019] Preferably, the xylose residue powder is composed of 59.9% cellulose, 9.6% hemicellulose, and 21.5% lignin.

[0020] The above one or more technical solutions have the following beneficial effects:

[0021] (1) The present invention provides a method for producing oligosaccharide glucose and lignin from xylose residue. By precisely regulating the molar ratio of zinc bromide to water, a homogeneous and stable reaction system is formed under oscillating ultrasound conditions. At the same time, zinc bromide hydrate, as a powerful reaction medium and catalyst, deeply participates in the reaction. When treating xylose residue, its unique ionic composition can precisely target the chemical bonds within cellulose molecules, greatly promoting the hydrolysis reaction of cellulose to proceed in the direction of generating oligosaccharide glucose, changing the inefficient dilemma of the hydrolysis reaction in traditional processes.

[0022] (2) Compared with lithium bromide, zinc bromide molten salt hydrate can achieve a treatment effect similar to that of lithium bromide molten salt hydrate at a relatively lower temperature when treating xylose residue. The pH of zinc bromide molten salt hydrate is smaller and its acidity is stronger, without the need to additionally add acid, while using lithium bromide molten salt hydrate to treat xylose residue usually requires adding a small amount of acid.

[0023] (3) Experimental results show that the yield of oligosaccharide glucose with a degree of polymerization of 3 - 8 produced by the method provided by the present invention can reach up to 61.7 wt% (based on the mass of cellulose in xylose residue), and the yield of lignin can reach up to 95.8% (based on the mass of lignin in xylose residue). The present invention converts the resource - rich, low - cost, and renewable xylose residue waste raw material into high - value - added oligosaccharide glucose and lignin. The separation time is short, the separation method is simple and easy to implement, and the inorganic salt can be recycled, realizing the high - value comprehensive utilization of biomass resources and having good economic and environmental benefits. Description of the Drawings

[0024] The specification drawings forming a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention.

[0025] Figure 1 It is the degree - of - polymerization distribution of oligosaccharide glucose in Example 3 of the present invention. Detailed Description of the Invention

[0026] It should be noted that the following detailed description is illustrative and is intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present application belongs.

[0027] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular forms are also intended to include the plural forms. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they specify the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0028] The present invention will be further described in conjunction with specific examples. The following examples are only for explaining the present invention and do not limit its content. If the specific experimental conditions are not indicated in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the sales company; the materials, reagents, etc. used in the examples can be obtained through commercial channels without special instructions.

[0029] In view of the limited methods for treating xylose residues in the prior art, the present invention provides a method for producing oligo-glucose and lignin from xylose residues. By precisely controlling the molar ratio of zinc bromide to water, it is realized that only zinc bromide molten salt hydrate is used to treat the dried and pulverized xylose residue powder to produce oligo-glucose and high-purity and high-yield lignin. At the same time, oligo-glucose is separated by alcohol precipitation, and the zinc bromide molten salt hydrate is recycled through dialysis rotation.

[0030] Specifically, the embodiment of the present invention discloses a method for producing oligo-glucose and lignin from xylose residues, comprising the following steps:

[0031] (1) After drying, the xylose residue is pulverized to a particle size of 0.1 - 1 mm to obtain xylose residue powder;

[0032] (2) The xylose residue powder is added to zinc bromide molten salt hydrate and reacted at 80 - 110 °C for 20 - 60 minutes. After the reaction is completed, filtration and separation are carried out to obtain a liquid phase containing glucose and oligo-glucose and a solid phase rich in lignin; the liquid phase precipitates oligo-glucose with organic alcohol, and the polymerization degree distribution range of the obtained oligosaccharides is 2 - 12, and the solid phase is washed and dried to obtain lignin.

[0033] The method provided by the present invention uses xylose residues to produce oligo-glucose and lignin, and has the characteristics of high yield, simple and easy separation method, and the inorganic salt can be recycled.

[0034] In the process of producing oligo-glucose and lignin from xylose residues, the present application first performs a drying treatment on the xylose residues, and the dried xylose residues are pulverized to a particle size of 0.1 - 1 mm by a pulverizing device to obtain pretreated xylose residue powder.

[0035] In the above treatment process, the zinc bromide molten salt hydrate is ZnBr 2· 3 - 5H 2 O, wherein the preparation process of zinc bromide molten salt hydrate is as follows: Dissolve different masses of solid zinc bromide salt in deionized water, and ultrasonically oscillate until the solid is completely dissolved, and store it for subsequent experiments. The molar ratio of water to zinc bromide in the molten salt hydrate is 1:3 - 5, preferably 1:4.

[0036] In one or more embodiments of the present invention, the mass - volume ratio of the xylose residue powder to the zinc bromide hydrate is 1:10 - 30, g / mL.

[0037] In one or more embodiments of the present invention, the mass - volume ratio of the xylose residue powder to the zinc bromide hydrate is 1:20, g / mL.

[0038] In one or more embodiments of the present invention, in step (2), the reaction temperature is 80 - 110 °C, and the reaction time is 20 - 60 min.

[0039] In one or more embodiments of the present invention, in step (2), the reaction temperature is 100 °C, and the reaction time is 40 minutes.

[0040] In one or more embodiments of the present invention, in step (2), after the reaction is completed, the reaction system is rapidly cooled to room temperature, and filtration separation is used to obtain a liquid phase containing glucose and oligosaccharides and a solid phase rich in lignin.

[0041] For the liquid - phase product, an organic alcohol is added to precipitate the oligosaccharides, and then filtration separation is carried out; the precipitated part is oligosaccharides, and the distribution of oligosaccharides is detected by ion chromatography. The degree - of - polymerization distribution range of oligosaccharides is 2 - 12, and the yield is 51.6 - 61.7 wt% (based on the mass of cellulose in the xylose residue). Among them, the proportion of oligosaccharides with a degree of polymerization of 3 - 8 in all oligosaccharides is 75.1 - 78 wt%. The separated liquid is treated with a dialysis bag with a molecular weight of 100, the liquid outside the dialysis bag is collected, and the organic alcohol and water are removed by rotary evaporation to recover zinc bromide for reuse.

[0042] For the solid - phase product, it is washed with water multiple times to remove the residual molten salt hydrate and other impurities, and lignin is obtained after drying. Among them, the purity of lignin is 96.7 - 98.1%, and the yield is 94.7 - 95.8 wt% (based on the mass of lignin in the xylose residue); the liquid after precipitating the oligosaccharides is treated with a dialysis bag with a molecular weight of 100, the liquid outside the dialysis bag is collected, and the organic alcohol and water are removed by rotary evaporation to recover zinc bromide for reuse.

[0043] In one or more embodiments of the present invention, the organic alcohol is one of methanol, ethanol, propanol, or butanol, preferably methanol.

[0044] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0045] Example 1

[0046] The xylose residue was washed with water multiple times (to remove impurities), dried to a constant weight at 60 °C, and then crushed by a crushing device to a particle size of 0.1 - 1 mm to obtain pretreated xylose residue powder. The cellulose in the xylose residue powder was measured to be 59.9 wt%, hemicellulose was 9.6 wt%, and lignin was 21.5 wt% using the biomass component determination method (NREL / TP - 510 - 42618).

[0047] Example 2

[0048] 225.18 g of ZnBr 2 was added to 54 g of deionized water, and the mixture was sonicated with oscillation until the solid was completely dissolved to prepare a zinc bromide molten salt hydrate (ZnBr 2 ·3H 2 O). 5 g of the pretreated xylose residue powder from Example 1 was weighed and added to 100 mL of the zinc bromide molten salt hydrate (ZnBr 2 ·3H 2 O), with a solid - liquid ratio of 1:20. The reaction was carried out at 90 °C for 40 minutes. After the reaction ended, the reaction system was quickly cooled to room temperature, and then filtered. The liquid phase containing glucose and oligosaccharides and the solid phase rich in lignin were separated by filtration.

[0049] Methanol was added to the separated liquid - phase product, and the mass - to - volume ratio of the liquid - phase product to methanol was 1:15, g / mL. Oligosaccharides were precipitated, and the yield of oligosaccharides was 52.3 wt% (based on the mass of cellulose in the xylose residue). The distribution of oligosaccharides was detected by ion chromatography. The degree - of - polymerization distribution range of oligosaccharides was 2 - 12, and the proportion of oligosaccharides with a degree of polymerization of 3 - 8 in all oligosaccharides was 75.1%.

[0050] The liquid after precipitating oligosaccharides was treated with a dialysis bag with a molecular weight cut - off of 100. The liquid outside the dialysis bag was collected, mainly containing the molten salt hydrate and methanol. The organic alcohol and water were removed by rotary evaporation, and zinc bromide was recovered for reuse.

[0051] For the solid - phase product, it was washed with water multiple times to remove the residual molten salt hydrate and other impurities, and lignin was obtained after drying. The purity of lignin was 96.7%, and the yield was 95.2 wt% (based on the mass of lignin in the xylose residue).

[0052] Example 3

[0053] Add 225.18 g of ZnBr 2 to 72 g of deionized water, and dissolve the solid completely by oscillating and ultrasonicating to prepare a zinc bromide molten salt hydrate (ZnBr 2 ·4H 2 O). Weigh 5 g of the pretreated xylose residue powder in Example 1 and add it to 100 mL of the zinc bromide molten salt hydrate (ZnBr 2 ·4H 2 O), with a solid-liquid ratio of 1:20, and react at 100 °C for 40 minutes. After the reaction, quickly cool the reaction system to room temperature, and then filter. The filtration separates a liquid phase containing glucose and oligosaccharides and a solid phase rich in lignin.

[0054] Add methanol to the separated liquid phase product, with a mass-volume ratio of the liquid phase product to methanol of 1:15, g / mL. Precipitate the oligosaccharides, and the yield of the oligosaccharides is 61.7 wt% (based on the mass of cellulose in the xylose residue). Use ion chromatography to detect the distribution of the oligosaccharides. The degree of polymerization distribution range of the oligosaccharides is 2-12, and the proportion of the oligosaccharides with a degree of polymerization of 3-8 in all the oligosaccharides is 78%.

[0055] Treat the liquid after precipitating the oligosaccharides with a dialysis bag with a molecular weight of 100, collect the liquid outside the dialysis bag, which is mainly the molten salt hydrate and methanol, and remove the organic alcohol and water therein by rotary evaporation to recover zinc bromide for reuse.

[0056] For the solid phase product, wash it repeatedly with water to remove the residual molten salt hydrate and other impurities, and dry it to obtain lignin. The purity of the lignin is 97.2%, and the yield is 95.8 wt% (based on the mass of lignin in the xylose residue).

[0057] Example 4

[0058] Add 225.18 g of ZnBr 2 to 63 g of deionized water, and dissolve the solid completely by oscillating and ultrasonicating to prepare a zinc bromide molten salt hydrate (ZnBr 2 ·3.5H 2 O). Weigh 5 g of the pretreated xylose residue powder in Example 1 and add it to 100 mL of the zinc bromide molten salt hydrate (ZnBr 2 ·3.5H 2 O), with a solid-liquid ratio of 1:20, and react at 110 °C for 40 minutes. After the reaction, quickly cool the reaction system to room temperature, and then filter. The filtration separates a liquid phase containing glucose and oligosaccharides and a solid phase rich in lignin.

[0059] Methanol was added to the separated liquid-phase product, and the mass-volume ratio of the liquid-phase product to methanol was 1:15, g / mL. Oligosaccharides were precipitated, and the yield of oligosaccharides was 51.6 wt% (based on the mass of cellulose in xylose residue). The distribution of oligosaccharides was detected by ion chromatography. The degree of polymerization distribution range of oligosaccharides was 2 - 12, and the proportion of oligosaccharides with a degree of polymerization of 3 - 8 in all oligosaccharides was 72.3%.

[0060] The liquid after the precipitation of oligosaccharides was treated with a dialysis bag with a molecular weight of 100, and the liquid outside the dialysis bag was collected, mainly molten salt hydrate and methanol. The organic alcohol and water were removed by rotary evaporation, and zinc bromide was recovered for reuse.

[0061] For the solid-phase product, it was washed with water multiple times to remove the residual molten salt hydrate and other impurities, and lignin was obtained after drying. The purity of lignin was 98.1%, and the yield was 94.7 wt% (based on the mass of lignin in xylose residue).

[0062] Example 5

[0063] The zinc bromide hydrate and the experimental method were the same as in "Example 3", except that the xylose residue powder and zinc bromide hydrate (ZnBr 2 ·4H 2 O) were reacted at 110 °C for 40 minutes.

[0064] Among them, after the liquid-phase product was precipitated with methanol, the yield of oligosaccharides was 58.6 wt% (based on the mass of cellulose in xylose residue). The distribution of oligosaccharides was detected by ion chromatography. The degree of polymerization distribution range of oligosaccharides was 2 - 12, and among them, the proportion of oligosaccharides with a degree of polymerization of 3 - 8 in all oligosaccharides was 73.1%.

[0065] The purity of the lignin obtained after washing and drying the solid-phase product was 97.4%, and the yield was 95.4 wt% (based on the mass of lignin in xylose residue).

[0066] It shows that the increase in temperature causes the further degradation of oligosaccharides into monosaccharides, and the yield of oligosaccharides is lower than that of the oligosaccharides in Example 3. It has little effect on the yield of lignin.

[0067] Example 6

[0068] The experimental method and experimental conditions were the same as in "Example 3", except that the zinc bromide hydrate was ZnBr 2 ·3H 2 O.

[0069] Among them, after the liquid-phase product was precipitated with methanol, the yield of oligosaccharides was 56.6 wt% (based on the mass of cellulose in xylose residue). The distribution of oligosaccharides was detected by ion chromatography. The degree of polymerization (DP) of oligosaccharides ranged from 2 to 12. Among them, the proportion of oligosaccharides with a DP of 3 to 8 accounted for 72.5% of all oligosaccharides.

[0070] The purity of lignin obtained after washing and drying the solid-phase product was 97.2%, and the yield was 95.3 wt% (based on the mass of lignin in xylose residue).

[0071] It shows that increasing the molar amount of water can increase the yield of oligosaccharides (the yield in Example 3 (ZnBr 2 ·3H 2 O) is higher than that in this example (ZnBr 2 ·3H 2 O)). Lower temperature reduces the yield of oligosaccharides (the yield in this example (100 °C) is higher than that in Example 2 (90 °C)).

[0072] Example 7

[0073] The experimental method and conditions were the same as those in "Example 3", except that the zinc bromide hydrate was ZnBr 2 ·5H 2 O.

[0074] Among them, after the liquid-phase product was precipitated with methanol, the yield of oligosaccharides was 54.7 wt% (based on the mass of cellulose in xylose residue). The distribution of oligosaccharides was detected by ion chromatography. The degree of polymerization (DP) of oligosaccharides ranged from 2 to 12. Among them, the proportion of oligosaccharides with a DP of 3 to 8 accounted for 70.7% of all oligosaccharides.

[0075] The purity of lignin obtained after washing and drying the solid-phase product was 96.9%, and the yield was 94.2 wt% (based on the mass of lignin in xylose residue).

[0076] It shows that when the molar amount of water is too high, the yield of oligosaccharides decreases instead, and it has little effect on the yield of lignin.

[0077] Comparative Example 1

[0078] The zinc bromide hydrate and the experimental method were the same as those in "Example 3", except that the xylose residue powder and the zinc bromide hydrate (ZnBr 2 ·4H 2 O) were reacted at 130 °C for 40 minutes. After the reaction, the reaction system was quickly cooled to room temperature.

[0079] Among them, after the liquid-phase product was precipitated with methanol, the yield of glucose was 76.8 wt%, and the yield of oligosaccharides was 8.9 wt% (based on the mass of cellulose in xylose residue). This indicates that oligosaccharides were further degraded to glucose at a relatively high temperature.

[0080] For the solid-phase product, it was washed with water multiple times to remove residual molten salt hydrates and other impurities, and then dried. The purity of lignin was 97.7%, and the yield was 95.3 wt% (based on the mass of lignin in xylose residue).

[0081] Comparative Example 2

[0082] 86.84 g of LiBr was added to 54 g of deionized water, and the mixture was sonicated with oscillation until the solid was completely dissolved to prepare a lithium bromide molten salt hydrate (LiBr·3H 2 O). 5 g of the pretreated xylose residue powder in Example 1 was weighed and added to 100 mL of the lithium bromide molten salt hydrate (LiBr·3H 2 O), with a solid-liquid ratio of 1:20. The reaction was carried out at 110 °C for 60 minutes. After the reaction, the reaction system was quickly cooled to room temperature, and filtration was used to separate a liquid phase containing glucose and oligosaccharides and a solid phase rich in lignin. Among them, after the liquid-phase product was precipitated with methanol, the yield of glucose was 10.8 wt%, and the yield of oligosaccharides was 3.5 wt% (based on the mass of cellulose in xylose residue).

[0083] For the solid-phase product, it was washed with water multiple times to remove residual molten salt hydrates and other impurities, and then dried. The yield of lignin was 53.7% (based on the mass of lignin in xylose residue).

[0084] Analysis of the hydrolysis solution and solid product showed that the LiBr·3H 2 O molten salt hydrate could not effectively hydrolyze cellulose into oligosaccharides, and a large amount of cellulose remained unhydrolyzed and was retained in the solid residue.

[0085] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A method for producing oligoglucose and lignin using xylose residues, characterized in that: The method comprises the following steps: (1) drying the xylose residue and crushing it into a particle size of 0.1-1 mm to obtain xylose residue powder; (2) adding the xylose residue powder to zinc bromide molten salt hydrate, reacting at 80-110° C. for 20-60 minutes, filtering and separating after the reaction to obtain a liquid phase containing glucose and oligoglucose and a solid phase containing lignin; precipitating the oligoglucose in the liquid phase with an organic alcohol, and obtaining an oligoglucose with a degree of polymerization distribution range of 2-12; and washing and drying the solid phase to obtain lignin.

2. The method according to claim 1, characterized in that The zinc bromide molten salt hydrate is ZnBr2·3-5H2O.

3. The method according to claim 1, characterized in that The distribution range of the degree of polymerization of the oligoglucose is 3-8.

4. The method according to claim 1, characterized in that The purity of the lignin is greater than 96%, and the yield is greater than 94%.

5. The method according to claim 1, characterized in that In step (2), the reaction temperature is 80-110° C., and preferably, the reaction time is 20-60 minutes; preferably, the reaction temperature is 100° C., and the reaction time is 40 minutes.

6. The method according to claim 1, characterized in that In step (2), the organic alcohol is one of methanol, ethanol, propanol or butanol.

7. The method according to claim 6, characterized in that In step (2), the organic alcohol is methanol.

8. The method according to claim 1, characterized in that In step (2), the liquid after the oligoglucose is precipitated is treated with a dialysis bag with a molecular weight of 100, the liquid outside the dialysis bag is collected, the organic alcohol and water therein are removed by rotary evaporation, and the zinc bromide is recovered for reuse.

9. The method according to claim 1, characterized in that In step (2), the solid portion obtained by filtration is washed with distilled water.

10. The method according to claim 1, characterized in that The xylose residue powder consists of 59.9% cellulose, 9.6% hemicellulose and 21.5% lignin.